2002
DOI: 10.2298/mpns0212475p
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vitiligo

Abstract: Our results show that segmental vitiligo and halo nevi occurred significantly more often in children than adults with vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…One hundred and twenty eight (17%) vitiligo patients were considered to have a family history and 28 (4.2%) cases have other auto-immune diseases. Patients were considered to have early onset vitiligo (n = 384, 61.4%) if the age of onset was prior to 20 years old [25].…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and twenty eight (17%) vitiligo patients were considered to have a family history and 28 (4.2%) cases have other auto-immune diseases. Patients were considered to have early onset vitiligo (n = 384, 61.4%) if the age of onset was prior to 20 years old [25].…”
Section: Resultsmentioning
confidence: 99%
“…A positive family history of thyroid disease has been described in 32% to 43% of children with vitiligo, but in our study, no significant difference was observed in the family history of vitiligo in either group. 12 , 19 A positive family history for the premature greying of hairs is more common in the prepubertal vitiligo group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose age of onset was earlier than 20 years were considered to have early-onset vitiligo (n = 598, 59Á8%). 35 In addition, there were 27 (2Á7%) patients with vitiligo accompanied by autoimmune disease, including four cases of psoriasis, eight cases of hyperthyroidism, five cases of alopecia areata, five cases of rheumatoid arthritis, one case of scleroderma, three cases of atopic dermatitis and one case of diabetes mellitus.…”
Section: Characteristics Of Study Subjectsmentioning
confidence: 99%